FOOD AND BEVERAGE MANAGEMENT IN TOURISM: BUSINESS, MANAGEMENT AND ACCOUNTING A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Ida Ayu Sulastri; I Gusti Nyoman Wiantara; Ni Nyoman Rusmiati (Journal Research of Management, 2026)
This study aims to map the scholarly development of food and beverage management in tourism from a business, management, and accounting perspective by identifying its conceptual structure, intellectual structure, collaboration patterns, and future research directions. The study employed a systematic literature review approach following PRISMA 2020 and integrated it with bibliometric analysis using RStudio and the Bibliometric package. Data were collected from the Scopus database through a search of English-language journal articles published between 2020 and 2026 within the Business, Management and Accounting subject area. After the identification, screening, and eligibility procedures, a final corpus of 93 articles was retained for analysis. The findings indicate that food and beverage management in tourism has developed from a relatively narrow operational concern into a more visible and strategically significant research field. Conceptually, the literature is structured around three dominant themes: food tourism, marketing, and cultural heritage; sustainability, ecotourism, and destination management; and experience, authenticity, and co-creation. Intellectually, the field is supported by interconnected streams related to culinary experience, sustainable operations, destination development, managerial resilience, and digital innovation. The collaboration structure further reveals that knowledge production remains concentrated in a limited number of countries, particularly Italy and the United Kingdom, while emerging contributors such as Indonesia are growing but remain comparatively fragmented. These findings confirm the strategic role of food and beverage management in destination value creation and suggest that future research should prioritize digitalization, operational sustainability, food waste governance, and community-linked co-creation.